Effect of various temperatures on the postharvest quality and storage life of persimmon fruit - Iqbal, Mussawer; Bibi, Farzana; Naeem, Muhammad; Khan, Muhammad Ayaz; Khan , Rahmatullah (Journal of Postharvest Technology, 2019)
An experiment was conducted to find out the “effect of various temperatures on the postharvest quality and storage life of persimmon fruit” at Post Harvest Horticulture Laboratory, The University of Agriculture Peshawar, during 2016. The experiment was laid down in Completely Randomized Design (CRD) having two factor replicated thrice. Persimmon fruits were stored at different temperatures (10°C RH=89±1, 20°C RH=79±1 and 30°C RH=69±1) and storage durations (0, 6, 12, 18, 24, 30 and 36 days). Fruits were analyzed for different physico-chemical attributes after each 6 days of storage durations. Temperature show significant effect on the quality attributes of persimmon fruit. Maximum value of fruit firmness (3.75 kg/cm2 ), ascorbic acid content (37.68 mg/100g), moisture content (71.47%) and titratable acidity (0.24%) with minimum weight loss (8.09%), waste percent (3.8%), color score (3.19), taste score (3.44), total soluble solids (TSS) (17.76 °brix) and pH (5.84) were noted in fruits stored at 10°C. Quality attributes were significantly influenced by storage durations. The highest fruit firmness (4.07 kg/cm2), moisture content (76.81%), titratable acidity (0.30%) and ascorbic acid content (50.44 mg/100g) with minimum value of TSS (15.27 °brix), pH (5.27), weight loss (0.00%), waste percent (0.00%), color score (1.66) and taste score (1.72) were found in fresh fruits. The interaction showed significant effect on all quality parameters. The highest fruit firmness (3.23 kg/cm2), moisture percent (64.22%), titratable acidity (0.18%) and ascorbic acid content (22.22 mg/100g) with minimum value of TSS (21.66 °brix), pH (6.29), weight loss (19.17%), waste percent (17.77%), color score (5.51) and taste score (5.50) were found in fruits on 36 days of storage durations at 10°C. The overall results revealed that fruits stored at 10°C maintained all the qualitative attributes of persimmon fruits up to 36 days storage durations.